PENERAPAN E-LEARNING SEBAGAI PENDUKUNG ADAPTIVE LEARNING DAN PENINGKATAN KOMPETENSI SISWA SMK DI KABUPATEN BANTUL - Nuur Wachid Abdulmajid; Andri Pramuntadi; Ari Budi Riyanto; Eliya Rochmah (Jurnal Taman Vokasi, 2017)
This research aims to know the application of e-learning for students’s SMK in Kabupaten Bantul. The research used the qualitative case study approach. This research took place at SMK Muhammadiyah 1 Imogiri Bantul. The informants in this research were expert technician of IT, lecuture of IT/IS, teachers in SMK, and studets in SMK.. The data were collected through observation, in-depth interviews, and documentation. The technical analysis of the data refered to the analysis of Miles & Huberman interactive model, including data collection, data condensation, data display, and drawing and verifying conclusions. The result shows that: (1) Students's competence can be improved through the help of e-learning. The e-learning features can be used by students to learn independently or collaboratively; (2) Characteristics and different functions in Edmodo and Moodle make teachers can choose one or even both as a medium of online learning to support adaptive learning students's SMK.